Proteomic characterisation of leech microglia extracellular vesicles (EVs): comparison between differential ultracentrifugation and Optiprep™ density gradient isolation. Issue 1 (1st January 2019) - Arab, T; Raffo-Romero, A; Van Camp, C; Lemaire, Q; Le Marrec-Croq, F; Drago, F; Aboulouard, S; Slomianny, C; Lacoste, A-S; Guigon, I; Touzet, H; Salzet, M; et al.
ABSTRACT: In Mammals, microglial cells are considered as the resident immune cells in central nervous system (CNS). Many studies demonstrated that, after injury, these cells are activated and recruited at the lesion site. Leech microglia present a similar pattern of microglial activation and migration upon experimental lesion of CNS. This activation is associated with the release of a large amount of extracellular vesicles (EVs). We collected EVs released by microglia primary culture and compared two different protocols of isolation: one with differential ultracentrifugation (UC) and one using an additional Optiprep™ Density Gradient (ODG) ultracentrifugation. Nanoparticles tracking analysis (NTA) and transmission electron microscopy (TEM) were used to assess vesicles size and morphology. The protein content of isolated EVs was assessed by mass spectrometry approaches. Results showed the presence of EV-specific proteins in both procedures. The extensive proteomic analysis of each single ODG fractions confirmed the efficiency of this protocol in limiting the presence of co-isolated proteins aggregates and other membranous particles during vesicles isolation. The present study permitted for the first time the characterisation of microglial EV protein content in an annelid model. Interestingly, an important amount of proteins found in leech vesicles was previously described in EV-specific databases. Finally, purified EVs were assessed for neurotrophic activity and promote neurites outgrowth on primary cultured neurons.